PHC462 : Pharmaceutical biochemistry / Faculty of Pharmacy - UiTM, Faculty of Pharmacy (Universiti Teknologi MARA (UiTM), 2023)
This course provides an introduction to the biochemistry, cellular biochemistry and its application in pharmaceutical field. The structure and metabolism of carbohydrates, amino acids and proteins, lipids, and nucleic acids is explained in details. The chemistry of enzymes, its nomenclature and properties are discussed. The understanding of biomolecules’ metabolism integration and its relationship with hormones and vitamins is also taught in this course.